(untitled)
In many countries the government supports individuals' and companies' donations dedicated to charity organizations or more general to public goods. Yet the effects of governmental support with respect to the provision of public goods has been and still is subject to an extensive debate in the economic literature. Starting from Warr's (1982, 1983) famous neutrality result an array of conditions has been identified under which this result holds or not. In this paper we examine the commonly used policy approach to subsi- dize the private provision of public goods by granting agents deductions with respect to their income or corporate tax burden. We especially take into ac- count that most income tax schemes are progressive and that deductibility is limited. The problems that arise from these specific properties of the con- sidered tax-refund schemes are pointed out first. We then turn towards the effects which such a tax-refund scheme has with respect to the provision of the public good on the one hand and individual as well as aggregate wel- fare on the other hand. We show that the effects of this commonly practised method of supporting private public good provision depend crucially on the specific properties of the progressive tax scheme and the preference structure of agents. While Pareto-improvements and even Pareto-efficiency can result from the implementation of such a scheme, it is also conceivable that at least some agents perceive a utility reduction. Due to the dependency of welfare effects on the tariff structure, income tax reforms as they are planned in many countries might not only induce a reduction in private public good provision, but might also alter the induced welfare effects., address = Zurich, author = Karen Pittel and Dirk T.G. Rübbelke, copyright = http://www.econstor.eu/dspace/Nutzungsbedingungen, doi = 10.3929/ethz-a-004933248, keywords = H23; H42; 330; public goods; sponsoring; neutrality; Öffentliche Güter; Fundraising; Steuerpolitik; Philanthropie, language = eng, number = 04/34, publisher = ETH Zurich, CER-ETH - Center of Economic Research, title = Private Provision of Public Goods : Incentives for Donations, type = Economics Working Paper Series, url = https://hdl.handle.net/10419/171478, year = 2004